The Cobb-Douglas Marriage Matching Function: Marriage Matching with Peer and Scale Effects - Mourifié, Ismael; Siow, Aloysius (Journal of Labor Economics, 2021)
Across states, there is little correlation between a state’s marriage rate or cohabitation rate and own population. Within states, there is a positive (no) correlation between a state’s marriage (cohabitation) rate and its population growth rate. The Cobb-Douglas marriage matching function (CDMMF), which extends the Choo-Siow MMF to include peer effects, can rationalize these correlations. The model is easy to estimate. The CDMMF is estimated using panel data across US states from 1990 to 2010. The estimated model replicates the above scale effects. These effects are not sufficient to explain the large recent declines in the gains to marriage.